DEMNUni: comparing nonlinear power spectra prescriptions in the presence of massive neutrinos and dynamical dark energy. Issue 11 (1st November 2022) - Parimbelli, G.; Carbone, C.; Bel, J.; Bose, B.; Calabrese, M.; Carella, E.; Zennaro, M.
Abstract: We provide an accurate comparison, against large cosmological N -body simulations, of different prescriptions for modelling nonlinear matter power spectra in the presence of massive neutrinos and dynamical dark energy. We test the current most widely used approaches: fitting functions (HALOFIT and HMcode), the halo-model reaction (ReACT ) and emulators (baccoemu and EuclidEmulator2). Focussing on redshifts z ≤ 2 and scales k ≲ 1 h /Mpc (where the simulation mass resolution provides ∼ 1% accuracy), we find that HMcode and ReACT considerably improve over the HALOFIT prescriptions of Smith and Takahashi (both combined with the Bird correction), with an overall agreement of 2% for all the cosmological scenarios considered. Concerning emulators, we find that, especially at low redshifts, EuclidEmulator2 remarkably agrees with the simulated spectra at ≲ 1% level in scenarios with dynamical dark energy and massless neutrinos, reaching a maximum difference of ∼ 2% at z = 2. baccoemu has a similar behaviour as EuclidEmulator2, except for a couple of dark energy models. In cosmologies with massive neutrinos, at z = 0 all the nonlinear prescriptions improve their agreement with respect to the massless neutrino case, except for the Bird and TakaBird models which, however, are not tailored to w 0 – wa models. At z > 0 we do not find a similar improvement when including massive neutrinos, probably due to the lower impact of neutrino free-streaming at higher redshifts; rather at z = 2 EuclidEmulator2 exceeds 2% agreement for some dark energy equation of state. When considering ratios between the matter power spectrum computed in a given cosmological model and its ΛCDM counterpart, all the tested prescriptions agree with simulated data, at sub-percent or percent level, depending on z . Finally, we also test how nonlinear prescriptions compare against simulations when computing cosmic shear and angular galaxy clustering spectra. For the former, we find a 2–3% agreement for HMcode, baccoemu, EuclidEmulator2 and ReACT ; for the latter, due to the minimum stellar mass of the simulated galaxies, shot noise highly affects the signal and makes the discrepancies as high as 5%.